2003
DOI: 10.1080/14733140312331384372
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing gay affirmative therapy: An exploration of clients' views of what is helpful

Abstract: Gay affirmative therapy is a counselling approach that emphasises an affirming, non‐pathologising approach to therapeutic work with lesbian, gay and bisexual clients. In this study, lesbian and gay clients who had experienced counselling that they defined as affirming identified what they perceived to have been helpful. Questionnaires and interviews were used to collect the views of a sample of lesbian, gay and bisexual informants. The material gathered was analysed using a grounded theory approach, which gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…In this last theme, respondents identified the ways in which political awakening had impacted on them both personally and in terms of their increased understanding of the impact of oppression.Raised political awareness for those in the majority can lead to ‘politicized heterosexuality’ (Mohr, ), seeing sexual minorities as courageous survivors in an oppressed society, with a lack of appreciation of the complexity within lesbian, gay or bisexual groups. However, it is important that counsellors have educated themselves about the social context (Liddle, ), and the ways in which this impacts on sexual minorities (Pixton, ). Smetana and Bigner () take this one step further, suggesting a role for therapists in educating other professionals.…”
Section: Resultsmentioning
confidence: 99%
“…In this last theme, respondents identified the ways in which political awakening had impacted on them both personally and in terms of their increased understanding of the impact of oppression.Raised political awareness for those in the majority can lead to ‘politicized heterosexuality’ (Mohr, ), seeing sexual minorities as courageous survivors in an oppressed society, with a lack of appreciation of the complexity within lesbian, gay or bisexual groups. However, it is important that counsellors have educated themselves about the social context (Liddle, ), and the ways in which this impacts on sexual minorities (Pixton, ). Smetana and Bigner () take this one step further, suggesting a role for therapists in educating other professionals.…”
Section: Resultsmentioning
confidence: 99%
“…20 For example, research has shown that ‘gay affirmative therapy’ is preferred by LGB people as it views LGB lifestyles and sexual identities positively without pathologising them. 47 However, these findings come from qualitative studies with purposive samples. There needs to be a strong understanding of indigenous psychologies and the relationship between culture and psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of these LGBT-affirming environments, images, and literature can lead clients to feel marginalized, unwelcome, and can increase likelihood of internalized homophobia from living in a heterocentric society (Lindsay et al, 2011;Szymanski & Chung, 2008). Having a safe, confidential space is crucial in contributing to a strong therapeutic relationship and experience for lesbian women (Pixton, 2003).…”
Section: Create Affirmative Spacementioning
confidence: 99%